Bahyt Gafu`s documentary films (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to the work of Kazakhstan’s documentary filmmaker Bakhyt Gafu. The search for a director of formation, development and professional maturity to mainly conducted in two directions: journalism and ethnography. The director`s experiments in the nineties is to try to connect the complex imagery and poetization routine with risky aesthetics and new features of modern television and digital technology, which has led to a number of interesting documentary films. In the process of gaining authenticity, Visual Bahyta Gafu became more democratic and approachable, separated from the journalistic genre, from situational optical rhetoric and functional fixation circumstances.Key words: documentary, poetization routine, journalism, educational and ethnographic pictures, experiments, reality, pre-Islamic rituals and beliefs of the Kazakhs.